Real-world experience of first 100 bone marrow transplant (BMT) cases from a single centre in Bangladesh (Pulse, 2025)
Background: BMT also known as Hematopoietic stem cell transplant (HSCT) is a curative treatment modality for many benign and malignant diseases. In Bangladesh, HSCT started from 2014 and till today only 6 centres are doing the procedure. Evercare hospital (previously known as Apollo hospital) is advanced among all of them and by 2023, completed 100 cases of HSCT starting from 2016. This retrospective study aims to analyse the outcome of first 100 transplants performed over 8 years (from 2016 to 2024) and data also compared with major transplant registries available worldwide. Results: Among these 100 patients, 61 cases were autologous SCT (auto-SCT) and 39 were allogeneic SCT (allo-SCT). Auto-SCT done mostly for Multiple myeloma and lymphoma. The median follow-up period was 18.6 months, overall survival (OS) was 72%, and disease-free survival (DFS) was 62.3%. Transplant-related mortality was seen in 2 (3.3%) patients, both due to relapse. Out of 39 allo-SCT patients, 27 were from matched sibling donors (MSD), and 12 from haploidentical (haplo) donors. The median follow-up period was 15 months, OS was 54%, and DFS 48.7%. The survival of MSD and Haplo-SCT patients were compared, for MSD at a median follow-up of 10.5 months, OS was 52% and DFS was 48.1%, and for Haplo-SCT at a median follow-up of 19.5 months, OS was 58.3% and DFS 50%. Conclusion: This survey provides real data about the current activities of HSCT from a tertiary care centre in Bangladesh and will help physicians to understand the challenges of transplant process and its complications.Pulse Vol.17, 2025 P: 6-14